2016
DOI: 10.3390/s16081168
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Deflection of the Vertical for Improving Aerial Surveys: A Comparison between EGM2008 and ITALGEO05 Estimates

Abstract: Recent studies on the influence of the anomalous gravity field in GNSS/INS applications have shown that neglecting the impact of the deflection of vertical in aerial surveys induces horizontal and vertical errors in the measurement of an object that is part of the observed scene; these errors can vary from a few tens of centimetres to over one meter. The works reported in the literature refer to vertical deflection values based on global geopotential model estimates. In this paper we compared this approach wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…The Gravity Recovery and Climate Experiment (GRACE) gravity satellite program presents a new opportunity to monitor the change of the groundwater storage (GWS), which was jointly developed by the National Aeronautics and Space Administration (NASA) and the German Space Flight Center (DLR), and was successfully launched in March 2002 [3,4]. This satellite measures the time-varying gravitational field of the Earth, and it can be converted into the equivalent surface mass changes on Earth, which are mainly due to changes of terrestrial water storage (TWS).…”
Section: Introductionmentioning
confidence: 99%
“…The Gravity Recovery and Climate Experiment (GRACE) gravity satellite program presents a new opportunity to monitor the change of the groundwater storage (GWS), which was jointly developed by the National Aeronautics and Space Administration (NASA) and the German Space Flight Center (DLR), and was successfully launched in March 2002 [3,4]. This satellite measures the time-varying gravitational field of the Earth, and it can be converted into the equivalent surface mass changes on Earth, which are mainly due to changes of terrestrial water storage (TWS).…”
Section: Introductionmentioning
confidence: 99%
“…In the monograph of each Geodetic Point, all useful data are included. In particular, both the ellipsoidal and ortometric heights are present, the first resulting by accurate GPS survey, the latter measured by levelling or calculated using the accurate local geoid ItalGeo2005 whose differences compared to EGM2008 are well known in literature (Barzaghi et al, 2016). Differences between the ellipsoidal and orthometric heights are calculated to achieve geoid undulations.…”
Section: Resultsmentioning
confidence: 99%
“…This grid results as an integration of airborne, terrestrial and altimetry-derived gravity data. EGM2008 is complete to spherical harmonic degree and order 2159 and encloses additional coefficients up to degree 2190 and order 2159 (Pavlis, Holmes, Kenyon, & Factor, 2012;Barzaghi, Carrion, Pepe, & Prezioso, 2016).…”
Section: Egm2008 Geoid Undulationmentioning
confidence: 99%
“…In a region where the anomalous gravity field is relevant, it is necessary to modify Equation (9) to take this phenomenon into account. Indeed, recent studies about the impact of the anomalous gravity field in GNSS/INS applications (Barzaghi, Carrion, Pepe, & Prezioso, 2016) have shown that neglecting the impact of the Deflection-of-Vertical (DoV) in aerial surveys induces horizontal and vertical errors in the measurement of an object that is part of the observed scene, which might vary from a few tens of centimetres to over 1 m. To improve the accuracy of the GNSS/INS approach, a corrective rotation matrix may be introduced in Equation (9) to account for the transformation from the local level frame to the ellipsoidal frame (Pepe, Prezioso, & Santamaria, 2015).…”
Section: Review Of Software For Flight Planningmentioning
confidence: 99%